2014
DOI: 10.1016/j.bone.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Increasing shape modelling accuracy by adjusting for subject positioning: An application to the analysis of radiographic proximal femur symmetry using data from the Osteoarthritis Initiative

Abstract: In total hip arthroplasty, the shape of the contra-lateral femur frequently serves as a template for preoperative planning. Previous research on contra-lateral femoral symmetry has been based on conventional hip geometric measurements (which reduce shape to a series of linear measurements) and did not take the effect of subject positioning on radiographic femur shape into account. The aim of this study was to analyse proximal femur symmetry based on statistical shape models (SSMs) which quantify global femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This study was conducted on radiographs of the OA–unaffected hip joint of subjects with unilateral hip OA on the assumption that the OA–unaffected side is a good predictor of the shape of the affected side before disease. This assumption was based on our prior analyses of the 2‐dimensional radiographic shape of left and right proximal femurs as captured by an SSM . Assuming radiographic proximal femur symmetry before the onset of disease, this raises questions as to what determines which side (left/right) will first develop OA, whether carriers of the risk allele of a susceptibility SNP are more prone to develop bilateral hip OA over time, and at what stage the morphology of the femur reflects changes as a consequence of disease rather than a predisposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted on radiographs of the OA–unaffected hip joint of subjects with unilateral hip OA on the assumption that the OA–unaffected side is a good predictor of the shape of the affected side before disease. This assumption was based on our prior analyses of the 2‐dimensional radiographic shape of left and right proximal femurs as captured by an SSM . Assuming radiographic proximal femur symmetry before the onset of disease, this raises questions as to what determines which side (left/right) will first develop OA, whether carriers of the risk allele of a susceptibility SNP are more prone to develop bilateral hip OA over time, and at what stage the morphology of the femur reflects changes as a consequence of disease rather than a predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption was based on our prior analyses of the 2‐dimensional radiographic shape of left and right proximal femurs as captured by an SSM . Assuming radiographic proximal femur symmetry before the onset of disease, this raises questions as to what determines which side (left/right) will first develop OA, whether carriers of the risk allele of a susceptibility SNP are more prone to develop bilateral hip OA over time, and at what stage the morphology of the femur reflects changes as a consequence of disease rather than a predisposition. Future longitudinal studies will be needed to explore the interplay between genetically determined proximal femur morphology and the onset/progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty of Dentistry | University of Oslo | 2018 [36] also found that demographics (age, weight, height, ethnicity and gender) had no association with asymmetry. The bilateral matching symmetry of the femur is a valuable aid in reproducing the correct femoral size, shape and orientation in hip arthroplasty [37,38].…”
Section: Epithelial-mesenchymalmentioning
confidence: 99%
“…Although preoperative planning of hip replacement using the contralateral side is common [ 23 – 25 ], the lateral discrepancies in the 3-dimensional geometry of the proximal femur may generate inaccuracies in various template approaches [ 26 28 ]. There are limited data on the lateral variability of LTFHC and GTFHC [ 18 ].…”
Section: Discussionmentioning
confidence: 99%